2022
DOI: 10.1155/2022/8945423
|View full text |Cite
|
Sign up to set email alerts
|

Rib Fracture Detection with Dual-Attention Enhanced U-Net

Abstract: Rib fractures are common injuries caused by chest trauma, which may cause serious consequences. It is essential to diagnose rib fractures accurately. Low-dose thoracic computed tomography (CT) is commonly used for rib fracture diagnosis, and convolutional neural network- (CNN-) based methods have assisted doctors in rib fracture diagnosis in recent years. However, due to the lack of rib fracture data and the irregular, various shape of rib fractures, it is difficult for CNN-based methods to extract rib fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…To our knowledge, six prior studies used the RibFrac or other private institutional CT scan data sets to build rib fracture prediction algorithms. Five used U-Net or V-Net-based models; 5,7–11 these models approached fracture detection as a segmentation task, which lacks computational efficiency compared with object detection tasks. One study used a Faster R-CNN–based object detection model, 10 but FasterRib used a larger ResNet backbone and deeper classifier architecture to improve detection performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, six prior studies used the RibFrac or other private institutional CT scan data sets to build rib fracture prediction algorithms. Five used U-Net or V-Net-based models; 5,7–11 these models approached fracture detection as a segmentation task, which lacks computational efficiency compared with object detection tasks. One study used a Faster R-CNN–based object detection model, 10 but FasterRib used a larger ResNet backbone and deeper classifier architecture to improve detection performance.…”
Section: Discussionmentioning
confidence: 99%
“…Existing rib fracture detection algorithms posed detection as a segmentation task, wherein every pixel per CT scan slice require binarily labeling (1 for fracture, 0 otherwise). 5,[7][8][9][10][11] To mitigate computational cost, we reformulated the problem into one of object detection, whereby the model outputs bounding boxes around each fracture per slice (boxes formed by pixel coordinates of the upper left and bottom right extremes per predicted fracture).…”
Section: Deep Learning Algorithm-fracture Detectionmentioning
confidence: 99%
“…On the remaining 32 studies, a full-text assessment was performed, through which 20 more studies were excluded. In the end, 12 studies were included in the systematic review [17][18][19][20][21][22][23][24][25][26][27][28], all of which were identified in the initial search. Unpublished relevant studies were not obtained.…”
Section: Study Selectionmentioning
confidence: 99%
“…The reference standard was quite similar for all the included studies, and all of them were retrospective. The quality of the studies ranged from intermediate to high quality: 2 studies with intermediate quality [18,19] and 10 studies with high quality [17,[20][21][22][23][24][25][26][27][28].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation